A Ni2P nanosheet array integrated on 3D Ni foam: an efficient, robust and reusable monolithic catalyst for the hydrolytic dehydrogenation of ammonia borane toward on-demand hydrogen generation. Issue 32 (27th July 2016) - Tang, Chun; Xie, Lisi; Wang, Kunyang; Du, Gu; Asiri, Abdullah M.; Luo, Yonglan; Sun, Xuping
Abstract : A Ni2 P nanosheet array integrated on Ni foam performs as a catalyst for on-demand hydrogen production from ammonia borane with an initial turnover frequency of 42.3 mol(H2 ) mol(Ni2 P) −1 min −1 and an activation energy of 44.0 kJ mol −1 . Abstract : Ammonia borane (AB) has been considered as one of the most attractive candidates for chemical hydrogen-storage materials; it is highly desirable but still remains a huge challenge to design and develop highly active robust non-noble-metal catalysts for on-demand hydrogen generation from AB. In this work, we demonstrate that a Ni2 P nanosheet array integrated on 3D Ni foam is highly active and robust for the hydrolytic dehydrogenation of AB. This monolithic catalyst behaves as an on/off switch for on-demand hydrogen generation with a large initial turnover frequency of 42.3 mol(H2 ) mol(Ni2 P) −1 min −1 and a lower activation energy of 44.0 kJ mol −1 under ambient conditions, outperforming all reported Ni-based noble-metal-free catalysts and some noble-metal catalysts.